2017
DOI: 10.1139/cjce-2016-0286
|View full text |Cite
|
Sign up to set email alerts
|

Virtual structural health monitoring and remaining life prediction of steel bridges

Abstract: In this study a Structural Health Monitoring (SHM) system is combined with Bridge Weigh-inMotion (B-WIM) measurements of the actual traffic loading on a bridge to carry out a fatigue damage calculation. The SHM system uses the 'Virtual Monitoring' concept, where all parts of the bridge that are not monitored directly using sensors, are 'virtually' monitored using the load information and a calibrated Finite Element (FE) model of the bridge. Besides providing the actual traffic loading on the bridge, the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…However, previous studies in road and railway B-WIM [26] have shown that there is no obvious correlation between accuracy and the speed of the vehicle. The application of the B-WIM system in weighting vehicles at full highway speed (checked against static weights) is demonstrated in several studies [25,39]. The bridge is supported on four steel bearings, illustrated in Figure 5, two at each end.…”
Section: Rb-wim Installation and Testingmentioning
confidence: 99%
“…However, previous studies in road and railway B-WIM [26] have shown that there is no obvious correlation between accuracy and the speed of the vehicle. The application of the B-WIM system in weighting vehicles at full highway speed (checked against static weights) is demonstrated in several studies [25,39]. The bridge is supported on four steel bearings, illustrated in Figure 5, two at each end.…”
Section: Rb-wim Installation and Testingmentioning
confidence: 99%
“…A finite analysis was performed on cracked beam using ANSYS 18.1 to for estimation of residual life of cracked beam [1,16,17]. A transverse crack has width of 1.25 mm and depth of 2 mm was made at a distance of 150 mm from the fixed end of the beam for estimation of residual life of cracked beam.…”
Section: Residual Life Estimation Of Cracked Beammentioning
confidence: 99%
“…Weigh-in-Motion systems were initially developed for overload monitoring and control purposes. However data gathered from WIM systems have also been used for other purposes such as updating notional traffic load models for bridge design [11], developing a site-specific bridge load model [12], calculating a dynamic amplification factor for bridge design and/or assessment [13], planning and management of road infrastructure [14], and assessment of fatigue load calculations [15][16][17]. In recent studies, it has also been investigated for SHM purposes.…”
Section: Introductionmentioning
confidence: 99%